2017
DOI: 10.1093/intimm/dxx026
|View full text |Cite
|
Sign up to set email alerts
|

Splicing in immune cells—mechanistic insights and emerging topics

Abstract: Splicing mechanisms—relevance for immune cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 100 publications
(140 reference statements)
1
55
0
2
Order By: Relevance
“…Of the DU peaks, on average 20% were tagged as near an A-rich region, and potentially due to internal priming, while an average of 32% flanked the canonical polyA motif. Among the DTU genes, there were known examples of alternatively spliced genes in immune cells, including IKZF1 (Ikaros) and PTPRC (CD45) [29]. Although PTPRC gene expression is ubiquitous among immune cell types, we found we could distinguish clear patterns of alternative peak usage in monocytes compared to other cell types ( Figure 2E) according to t-SNE visualisations of relative peak expression, demonstrating that we are able to detect cell type gene expression activity masked when only considering an aggregate of the reads across a gene.…”
Section: Differential Transcript Usage Among Human Pbmcsmentioning
confidence: 99%
“…Of the DU peaks, on average 20% were tagged as near an A-rich region, and potentially due to internal priming, while an average of 32% flanked the canonical polyA motif. Among the DTU genes, there were known examples of alternatively spliced genes in immune cells, including IKZF1 (Ikaros) and PTPRC (CD45) [29]. Although PTPRC gene expression is ubiquitous among immune cell types, we found we could distinguish clear patterns of alternative peak usage in monocytes compared to other cell types ( Figure 2E) according to t-SNE visualisations of relative peak expression, demonstrating that we are able to detect cell type gene expression activity masked when only considering an aggregate of the reads across a gene.…”
Section: Differential Transcript Usage Among Human Pbmcsmentioning
confidence: 99%
“…29 The spliceosome involves multicomponent complexes including five snRNPs that coordinate mRNA splicing. 30 Our finding that components of the spliceosome are both up-regulated and found interacting with UBR5 in MCL cell lines identifies a new pathway of UBR5 involvement. The striking phenotype of IgD in HECT domain mutants supports defects in splicing since IgM and IgD are generated from alternative splicing of the heavy chain gene.…”
Section: Discussionmentioning
confidence: 77%
“…As a proof of the concept, we investigated PTPRC , one of the best-studied examples, to examine the isotypes in T cells. PTPRC is essential during lymphocyte differentiation, using exons 4, 5, and 6 variably(13, 30). Two transcript isoforms are highlighted according to ENSEMBL(24): PTPRC-209, which retains exons 4,5,6 and translates into protein isoform PTPRC-RABC, and PTPRC-201, which splices out all three exons and translates into PTPRC-RO ( Supplementary Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…The ImmGen Consortium integrated high-throughput data and revealed pervasive events of alternative splicing (AS) in T cells, with ~60% of genes showing different AS events linking to the differentiation of different T cell lineages(8). Multiple studies identified specific transcript isoforms involved in T cell-related biology(9), including T cell activation (1012), T cell differentiation(13, 14), and apoptosis(15). For instance, PTPRC , which encodes the transmembrane tyrosine phosphatase CD45, is critical for T cell receptor (TCR) signal transduction(16).…”
Section: Introductionmentioning
confidence: 99%